OPTIMALISASI PENGEMBANGAN UMKM BERBASIS DIGITALISASI OLEH BAGIAN KESEJAHTERAAN RAKYAT SEKRETARIAT DAERAH KOTA BANJAR - Yana Suryana; Garvera, R. Rindu (Jurusan Ilmu Pemerintahan Universitas Palanfka Raya, 2024)
The emergence of information and communication technology has brought a significant change to various sectors of life, one of which is the Micro, Small and Medium Enterprises (MSMEs) sector. Therefore, of course, it has become a necessity as well as an obligation for local governments to create a more adaptive and innovative MSME ecosystem. Digitalization is one of the alternatives in maintaining the sustainability of MSMEs themselves, especially in Banjar City. This article aims to describe the importance of developing a digital MSME ecosystem in Banjar City and its correlation with activities carried out by the People's Welfare Section of the Banjar City Regional Secretariat. The method used in this study uses qualitative research with a phenomenological approach. The data in this article is sourced from relevant literature and from the author's observations while involved in activities carried out by the People's Welfare Section of the Banjar City Regional Secretariat. This article concludes that in the context of developing a digital MSME ecosystem, the Banjar City Regional Government has made the necessary efforts to create the ecosystem. These efforts are carried out by building solid collaboration and synergy between various related stakeholders who contribute, in terms of facilitation, concepts and ideas. In addition, there is a need for monitoring and evaluation efforts so that the activities carried out by the People's Welfare Section of the Banjar City Regional Secretariat can remain on the desired plans and goals. This digital MSME concept can bring the economic sector in Banjar City to a better stage so that it can compete at the global level and have an impact on its own local communities.